« Défaire » la femme africaine : intersectionnalité performative dans les œuvres semi-autobiographiques de Calixthe Beyala et de Ken Bugul - Harinen, Kaiju (fi=Turun yliopisto|en=University of Turku|, 2018)
Undoing” the African Woman: Performative Intersectionality in Calixthe Beyala’s and Ken Bugul’s Semiautobiographical Literature The thesis studies francophone women’s literature. The focus of the thesis is on the semiautobiographical writings of the West African authors Calixthe Beyala and Ken Bugul. The research material consists of two novels written by Calixthe Beyala, L’Assèze l’Africaine (1994) and La Petite fille du réverbère (1998), and a trilogy written by Ken Bugul, Le Baobab fou (1982), Cendres et braises (1994) and Riwan ou le chemin de sable (1999). Since the focus of the study is on the authors’ public images and social status, interviews and other paratexts are used as research material. Beyala’s and Bugul’s novels focus on the feeling of otherness and discrimination related to “race”, gender, sexuality, social class and religion that the protagonists of the novels, young “black” women, experience in the context of postcolonial Europe and West Africa. In their works, the authors use strategic exoticism, performativity, irony, burlesque humour and storytelling to make the apparently invisible intersectional i.e. interlocking system of oppression visible. This thesis analyses Beyala’s and Bugul’s feminist ethos and presents the emancipatory solutions that they offer from the perspective of the abovementioned intersectional and multiple oppressions. The thesis also criticizes some ethnocentric perspectives of studies of francophone literature, where such studies set both the authors and the protagonists in the position of the Other. The theoretical and methodological framework of the research is based in an intersectional perspective, combined with postcolonial studies, the sociology of literature, and comparative literature. All of the thesis’ findings in some way involve the presence of a racialized and mystified gender identity and its performativity that are strategically deployed by the authors in order to critique invisible power structures. The thesis can be applied to criticism of ethnocentricity in francophone studies. It also serves as an opening for openly positioned and politically situated research, which makes intersectionality visible by providing examples of the process by which the interlocking system of oppression is revealed in francophone literature, particularly in Beyala’s and Bugul’s works.

Väitöskirjassa tutkitaan frankofonista naiskirjallisuutta. Tarkastelun kohteena on kahden länsi-afrikkalaisen kirjailijan, Calixthe Beyalan ja Ken Bugulin, osittain omaelämäkerrallinen tuotanto. Tutkimusaineisto koostuu Beyalan romaaneista: Assèze l’Africaine (1994) ja La Petite fille du réverbère (1998) sekä Bugulin trilogiasta: Le Baobab fou (1982), Cendres et braises (1994) ja Riwan ou le chemin de sable (1999). Kirjailijoiden julkisuuskuvaa ja yhteiskunnallista asemaa analysoitaessa aineistona käytetään myös Beyalan ja Bugulin haastatteluja ja muita paratekstejä. Romaanien keskeinen sisältö on teosten päähenkilön, nuoren ”mustaihoisen” naisen, vierauden kokemus kolonialismin jälkeisessä Euroopassa ja Länsi-Afrikassa sekä ”rotuun”, sukupuoleen, seksuaalisuuteen, sosiaaliseen luokkaan ja uskontoon kohdistuva syrjintä. Kirjailijat pyrkivät tekemään näkymättömältä vaikuttavan intersektionaalisen eli risteävän eriarvoisuuden teoksissaan näkyväksi strategisen eksotismin, performatiivisuuden, ironian, burleskin huumorin ja sadunkerronnan keinoja hyväksi käyttäen. Tutkimuksessa analysoidaan Beyalan ja Bugulin feminististä eetosta ja esitellään heidän tarjoamiaan emansipatorisia ratkaisumalleja edellä mainituista risteävien erojen näkökulmista käsin. Tutkimuksessa kritisoidaan myös tiettyjä frankofonisen kirjallisuudentutkimuksen etnosentrisiä lähestymistapoja, jotka asettavat sekä kirjailijat että heidän teostensa henkilöhahmot toiseutettuun asemaan. Tutkimuksen teoreettis-metodologinen viitekehys muodostuu intersektionaalisesta näkökulmasta, joka yhdistetään postkoloniaaliseen tutkimukseen, kirjallisuuden sosiologiaan sekä vertailevaan kirjallisuustieteeseen. Kaikki tutkimustulokset liittyvät tavalla tai toisella rodullistettuun ja mystifioituun sukupuoli-identiteettiin ja sen performatiivisuuteen, jonka avulla kirjailijat pyrkivät kyseenalaistamaan vallan näkymättömiä rakenteita. Tuloksia voidaan hyödyntää frankofonisen kirjallisuudentutkimuksen etnosentrisyyttä kritisoivassa tutkimuksessa. Väitöskirja toimii myös avauksena avoimesti asemoituneelle ja poliittisesti sitoutuneelle tutkimukselle, joka havainnollistaa intersektionaalisuutta ja antaa joitakin esimerkkejä, joiden avulla risteävää eriarvoisuutta tehdään näkyväksi frankofonisessa kirjallisuudessa, erityisesti Beyalan ja Bugulin teoksissa.